Rainfall runoff simulation using modified SCS-CN and HEC-HMS model in Kuantan watershed - Allyson, Hilbert (2015)
Kuantan watershed located in the flood prone area and experienced flood event almost every year due to monsoon season on the Peninsular Malaysia in month of November to February. Based on the condition of the watershed that has high probability in subjected to the flood occurrence, it shows that there was a need to develop a hydrologic model for the watershed. The study aims to develop the rainfall-runoff relationship using hydrological model and GIS in Kuantan watershed, assess the performance of HEC-HMS model in runoff prediction and evaluate the accuracy of modified SCS-CN in tropical area. HEC-HMS model was used to stimulate the storm event that occurs in the watershed based on the selected event where the calibration and validation also were carried out. The method used in the model was the SCS Unit Hydrograph for the Transform Method, SCS-CN as the Loss Method, and Lag Time as the Flood Routing Method. The simulation was carried out based on two selected storm event which was on the month of December 2006 and month of January 2012. The value of initial abstraction ratio used was 0.2 and 0.05 which the result based on both application of the ratio will be compared. The model was calibrated based on the antecedent moisture condition which considering the wet condition in the watershed which was known as AMC III, where the calculated curve number based on the land use and hydrological soil groups criteria was assumed in the normal condition. The efficiency of the simulated result over actual result was access using the Nash-Sutcliffe Efficiency (NSE). For the simulated result based on selected event, the NSE value for the model before and after calibration was range from 0.7 to 0.9 for both value of initial abstraction ratio which shows that the model perform well but the model seem to underestimate the actual peak discharge in the watershed. The efficiency for the model based on event on December 2006 was higher without calibration with initial abstraction ratio of 0.2 while for event on January 2012; the efficiency of the model was higher after the model calibrated which has almost the similar efficiency for both ratio of abstraction use. The application of two different equations to calculate the Lag Time also gives slight changes in the result as the used of Kirpich Equation gives a better result compare to the use of SCS Lag Equation for the prediction of the peak discharge.